COLLOCATIONAL ANALYSIS OF THE PRIMARY CONJUGATIONS OF THE CONCEPT OF FRIENDSHIP IN THE UZBEK AND GERMAN LANGUAGES (BASED ON THE VIEWS OF GERMAN LINGUISTS) (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article examines the theoretical foundations of the concept of collocation based on the views of German linguists such as Helbig, Hausmann, Firth, Benson, and others. Furthermore, it provides a comparative analysis of primary word combinations related to the concept of “friendship” in Uzbek and German. The study identifies lexical-semantic and cultural similarities and differences in the expression of the concept of friendship in both languages.